Latino city : immigration and urban crisis in Lawrence, Massachusetts, 1945-2000 - Barber, Llana (Justice, power, and politics., 2017)
"Interweaves the histories of U.S. urban crisis and imperial migration from Latin America. Pushed to migrate by political and economic circumstances shaped by the long history of U.S. intervention in Latin America, poor and working-class Latinos then had to reckon with the segregation, joblessness, disinvestment, and profound stigma that plagued cities during the crisis era, particularly in the Rust Belt. For many Puerto Ricans and Dominicans, there was no "American Dream" awaiting them in Lawrence; instead, Latinos struggled to build lives for themselves in the ruins of industrial America"--